Analysis of thermo-hydro-mechanical coupling characteristics of artificial freezing process under seepage effects - Chen, Peipei; Yin, Fengling; Wang, Manqi (Frontiers in Materials, 2025)
The application of thermo - hydro - mechanical coupling considering seepage effects is of great significance in engineering fields such as artificial freezing. Functions of fluid and solid density, viscosity, and porosity are established considering the influence of temperature, pressure, etc. Based on Darcy’s law, mass conservation, momentum conservation, and energy conservation, a thermo - hydro - mechanical coupling theoretical model considering seepage effects is derived. The finite element platform is redeveloped to numerically model the artificial freezing process under seepage effects and verify it through experiments. Subsequently, numerical calculations are carried out to analyze the influence of working conditions, and the impacts of seepage velocity, freezing temperature, and initial soil temperature on the freezing effect are obtained. The calculations show that: (1) As the seepage velocity increases, the convective heat transfer effect becomes more significant. The cooling effect generated by the freezing pipe is transmitted more rapidly through the soil, leading to the rapid expansion of the freezing front. However, when the seepage velocity exceeds the critical value, the soil layer becomes difficult to freeze. (2) The more freezing pipes there are, the more significant the freezing effect. The lower the temperature of the freezing pipes, the larger the freezing radius under the same freezing conditions. The lower the initial temperature of the soil, the more significant the freezing effect within the same freezing time. (3) Under the condition of a decrease in the grade difference, the difference in the freezing front under 9→6 m/d is always higher than that under 6→3 m/d; under the change of the grade difference of the initial soil temperature and the refrigerant temperature, the difference in the freezing front radius generally shows an increasing trend, whether for single pipe or double pipe cases.